2010
DOI: 10.1159/000321043
|View full text |Cite
|
Sign up to set email alerts
|

Di-Nucleotide Repeat Polymorphisms of the Insulin-Like Growth Factor-1 Gene and Their Association with IGF-1, Insulin-Like Growth Factor-Binding Protein-1 and Birth Size in a Sri-Lankan Cohort

Abstract: Background: Insulin-like growth factor (IGF)-I is implicated in fetal growth. Ethnic variations of IGF-1 have also been suggested. Di-nucleotide repeat polymorphisms of the IGF-1 gene or their association with IGF-1 levels and birth size have not been studied in Sri Lankans. Objectives: To describe IGF-1 di-nucleotide repeat polymorphisms and their association with IGF-1 and IGF-binding protein (IGFBP)-1 levels and birth size in a cohort of Sri Lankans. Methods: A cross-sectional study on 200 mother-newborn pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1

Year Published

2014
2014
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 61 publications
1
6
1
Order By: Relevance
“…Several studies have shown cord blood IGF-I also to be gender-specific with higher levels reported in females [3,19,20]. However, we did not observe a gender effect on cord blood IGF-I levels in our previous study [13]. Similarly, there are other studies in which male and female newborns were found to have comparable levels of cord blood IGF-I [21].…”
Section: Introductioncontrasting
confidence: 77%
See 4 more Smart Citations
“…Several studies have shown cord blood IGF-I also to be gender-specific with higher levels reported in females [3,19,20]. However, we did not observe a gender effect on cord blood IGF-I levels in our previous study [13]. Similarly, there are other studies in which male and female newborns were found to have comparable levels of cord blood IGF-I [21].…”
Section: Introductioncontrasting
confidence: 77%
“…110 healthy appropriately grown term (delivered 37 + 0 to 39 + 6 completed weeks) newborns born following a singleton uncomplicated pregnancy in healthy women were selected from a previous study [13], based on the availability of aliquots of cord plasma for determination of leptin and SLR levels. Samples were collected over a 2-year period between January 2007 and December 2008.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations